Recent Advances in C–Br Bond Formation - Wong, Jonathan; Yeung, Ying-Yeung (Synlett, 2021)
Organobromine compounds are extremely useful in organic synthesis. In this perspective, a focused discussion on some recent advancements in C–Br bond-forming reactions is presented.1 Introduction2 Selected Recent Advances2.1 Catalytic Asymmetric Bromopolycyclization of Olefinic Substrates2.2 Catalytic Asymmetric Intermolecular Bromination2.3 Some New Catalysts and Reagents for Bromination2.4 Catalytic Site-Selective Bromination of Aromatic Compounds2.5 sp3 C–H Bromination via Atom Transfer/Cross-Coupling3 Outlook
Keywords: bromine; bromination; alkenes; catalysis; halogens